Relationship among Culture, Education and Sports - Peter, Vijay Francis (International Research Journal of Management, IT & Social Sciences, 2015)
The purpose of this article is to place sport in a social, cultural and educational context. This implies definitions of culture, education and sport, and the academic association of each to the others. However, it is seen that culture, education and sport have commonly-held meanings which, in some cases, eradicate the need for further clarification. So, apart from defining these important concepts, this article will also deal with the pervading nature of sports in society, sport as a system of sub-cultures and the degree to which sport has become an important symbol for individuals and societies worldwide. Sports has a variety of functions for different segments of society and therefore different meanings to those different populations. Everyone knows what a culture is. Everyone knows what education is. And everyone knows what sports is. But everyone has slightly different definitions of culture, education and sports.